Sensitivity and specificity of strain rate for the early detection of left ventricular dysfunction in breast cancer patients receiving adjuvant treatment with adriamycin with or without trastuzumab. (14th October 2021) - Tettamanti, M E; Gimenez, I; Chacon, C; Nadal, J; Costanzo, V; Nervo, A; Losco, F; Chacon, R; Santos, D A
Abstract: Background: Medical literature states that a global longitudinal strain rate (GLS) <−19% and further reductions in relation with baseline GLS may predict long term left ventricular dysfunction in breast cancer patients receiving adjuvant treatment with Adriamycin (A) with or without trastuzumab (T). However, there is not strong evidence to support the use of this technique in daily clinical practice. Purpose: To analyze the sensitivity (S) and specificity (Sp) of GLS <−19% or its relative 10, 15 and 20% reduction form baseline, for the early detection of left ventricular dysfunction in breast cancer patients receiving adjuvant treatment with A with or without T. Methods: Patients were prospectively assessed with a cardiac echoDoppler + GLS at baseline, every 3 months during the first year and every 4 months thereafter. We assessed the S and Sp of GLS <−19% or its relative >10%, >15% and >20% reduction form baseline after treatment with A with or without T as predictors of cardiotoxicity (defined as a >10 percentage points decrease of left ventricular ejection fraction to a value below the lower normal limit with respect to baseline). Results: 136 out of 884 patients (16%) had GLS measured at each visit: 83 patients (60%) and 53 patients (40%) treated with A or A+T respectively. Patients were followed up to 31±6 months. Mean age was 51±12 years. The table shows the baseline characteristics of both groups. 10 out of 83 patients in group A (12%) and 18 out of 53 P in group A+T (34%) developed cardiotoxicity. Baseline left ventricular ejection fraction and GLS were 61±4, 7% and −20, 18±2, 6% in group A, and 58, 7±5, 8% and −19, 5±2, 6 post treatment. In this group, GLS S and Sp were 50 and 80%, respectively. In the group A+T, the best GLS cutoff was −19%, with a 60% sensitivity and 78% specificity. Conclusions: In our non-selected cohort of patients, nor GLS or its percentage reductions along follow up predicted the reduction of left ventricular ejection fraction and the developing of cardiotoxic ventricular dysfunction in breast cancer patients receiving adjuvant treatment with A with or without T. The systematic use of this tool should be further investigated and validated at each center to help establish its usefulness in daily practice. FUNDunding Acknowledgement: Type of funding sources: None.